1996
DOI: 10.1016/s0006-3495(96)79581-4
|View full text |Cite
|
Sign up to set email alerts
|

Ryanodine interferes with charge movement repriming in amphibian skeletal muscle fibers

Abstract: Cut twitch muscle fibers mounted in a triple Vaseline-gap chamber were used to study the effects of ryanodine on intramembranous charge movement, and in particular on the repriming of charge 1. Charge 1 repriming was measured either under steady-state conditions or by using a pulse protocol designed to study the time course of repriming. This protocol consisted of repolarizing the fibers to -100 mV from a holding potential of 0 mV, and then measuring the reprimed charge moving in the potential range between -4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Finally, it should be stressed that the overall details of how ryanodine affects SR calcium regulation in an intact fiber are certainly more complex than inferred from above. For instance, it is far from easy to speculate about how processes such as voltage-dependent inactivation of the voltage sensors, Ca 2ϩ -dependent inactivation of release channels, SR Ca 2ϩ depletion, retrograde signaling between release channels and voltage sensors (Gonzalez and Caputo, 1996) would modulate the overall effect of ryanodine and/or be affected in the presence of the alkaloid. Also, it is not clear whether or not ryanodine-bound, open-locked release channels are still sensitive to activation by Ca 2ϩ as there seems to be conflicting results between single channel data (Rousseau et al, 1987) and skinned fibers data (Oyamada et al, 1993).…”
Section: Figure 12mentioning
confidence: 99%
“…Finally, it should be stressed that the overall details of how ryanodine affects SR calcium regulation in an intact fiber are certainly more complex than inferred from above. For instance, it is far from easy to speculate about how processes such as voltage-dependent inactivation of the voltage sensors, Ca 2ϩ -dependent inactivation of release channels, SR Ca 2ϩ depletion, retrograde signaling between release channels and voltage sensors (Gonzalez and Caputo, 1996) would modulate the overall effect of ryanodine and/or be affected in the presence of the alkaloid. Also, it is not clear whether or not ryanodine-bound, open-locked release channels are still sensitive to activation by Ca 2ϩ as there seems to be conflicting results between single channel data (Rousseau et al, 1987) and skinned fibers data (Oyamada et al, 1993).…”
Section: Figure 12mentioning
confidence: 99%
“…The ECG findings were not reported. [ 33 , 34 ] SPRY1 R739H See findings of the L62F mutation. [ 31 ] P1 R1013Q, R1051P See findings of the L62F mutation.…”
Section: The Ryr2 Dysfunction and Cardiac Pathophysiological Conditionsmentioning
confidence: 99%
“…Thanks to the available 3D RyR1 and 2 structures, we now know that the majority of the RyR2 related CPVT mutations are located in domains involved in channel activation and gating including the pore, pseudo-voltage sensor and central domains (Fig. 1 ) [ 1 , 34 , 35 ]. A potential link between mutation localization and phenotype severity has been emphasized [ 36 ], in particular mutations in the C-terminal hot-spot domain being of greater risk to patients.…”
Section: The Ryr2 Dysfunction and Cardiac Pathophysiological Conditionsmentioning
confidence: 99%
“…With respect to Q β the major component of charge movement in amphibian muscle, a number of studies (García et al . 1991a; Gonzalez and Caputo 1996; Huang 1996; Huang 1998; Squecco et al 2004) have reported no appreciable effect of ryanodine (≤ 200 μM at 2–17°C for 25–120 minutes). However, Gonzales and Caputo (1996) reported that the recovery from depolarization-induced immobilization of Q β is inhibited by ryanodine treatment (100 μM, ~25 minutes at 10°C).…”
Section: Discussionmentioning
confidence: 99%
“…In regard to L-type Ca 2+ currents, previous studies of amphibian skeletal muscle have reported no effects of ryanodine (García et al . 1991a; Gonzalez and Caputo 1996), except for a for a ~5 mV depolarizing shift in activation (Squecco et al . 2004).…”
Section: Discussionmentioning
confidence: 99%